An equity parking area location model for transition from dockless to docked shared micromobility systems - Simona De Bartolomeo; Michele Ottomanelli; Leonardo Caggiani (npj Sustainable Mobility and Transport)
Abstract The rise of micromobility shared vehicles has brought about a number of economic, environmental and social benefits. Specifically, there are two types of sharing systems: station-based (docked) and free-floating (dockless) systems. Although the latter allow users to release the vehicle at the exact point of destination, on the other hand it has generated disorder and obstruction on streets, blocking vehicle flow and pavements. To solve this issue, it is necessary to locate stations where the vehicles must be picked up and released, so avoiding illegal user behaviour. However, the location of stations may generate inequalities, i.e. one part of the population may cover higher walking distances to reach a station. For this reason, we propose a bi-objective parking area location model for shared micromobility systems considering walking distance equity aspects to convert a free-floating system into station-based. This model has been applied to the city of Bari (Apulia, Italy).